Effectiveness of Content Booklets Conservation of Bryophyta Material in Gunung Kidul National Park Ciremai to Increase Student Science Literacy - Abdillah, Irkhamni; Irsadi, Andin (Unnes Science Education Journal, 2025)
Learning media is very important in help stimulate think critical students, research results about literacy science like effectiveness of Learning Booklets not yet applied in a way maximum in school. The purpose of study is to know effectiveness of booklet content conservation of Bryophyta material for increase ability literacy science students. The method used in this study is quantitative method. Quantitative methods is method research based on positivism, the method used to researching population or sample certain. Technique taking sample usually done with calculation technique appropriate sample. Quantitative data collection aiming for test hypothesis that has been set data literacy science based on the average value N-gain. Based on results can explained that, the effectiveness of the booklet contains conservation to increase literacy science class experiment more tall compared with class control. Learning using booklet learning media on Bryophyta material get strong response and got response positive from student.